The networking aspect of international students’ integration into Finnish working life : a case study of Team&Client project course - Arzamastseva, Elizaveta (2021)
This thesis explores how the social networks developed during Higher Education Studies contribute to international students’ integration into Finnish working life. Previous research provides evidence that international students experience difficulties with finding jobs in Finland after completing their studies, and the lack of social networks is recognized as one of the main employment barriers. According to the Strength of Weak Ties theory, weak social networks, especially when they connect representatives of different social groups, provide better employment outcomes for an individual. Team&Client project course organized by the University of Jyväskylä is used in this study as an example of a university course, where international students have an opportunity to create such ties.